Development Of Seismic Refraction Technique With Flexible Sources- Receivers Arrangement - Kiu, Yap Chong (2020)
Seismic refraction method is one of the most effective of all geophysical methods used to characterize ground subsurface. The restricted use of seismic refraction may due to some limitations associated with survey costs and inadequate flexibility of survey. This study outlines the development of a new approach in flexible sources-receivers arrangement for seismic refraction data acquisition technique. This new design is an innovative solution which implements only a few geophones to execute a full-length seismic refraction survey, with adequately similar data to pick first arrival time in order to overcome the limitations of coverage and inflexibility of the survey.